Evaluation of Microvascular Structure Changes after Conbercept Treatment on Macular Edema Secondary to Retinal Vein Occlusion. (20th June 2020) - Song, Wenqi; Jiao, Wanzhen; Li, Fengjiao; Ma, Aihua; Zhao, Bojun
Abstract : Aims. To confirm the therapeutic efficacy of conbercept for the treatment of macular edema (ME) secondary to retinal vein occlusion (RVO) by using optical coherence tomography angiography (OCTA) and to find out the differences in therapeutic efficacy between ischemic and nonischemic retinal vein occlusion (iRVO or non-iRVO) after conbercept treatment. Methods. In this prospective, randomized, and comparative study, 60 unilateral eyes suffered from RVO combined with macular edema were included and fellow eye as controls. After an initial intravitreal injection of conbercept (IVIC), a pro re nata (PRN) strategy was adopted, and the follow-up time was 6 months. The foveal avascular zone (FAZ), vascular density of superficial capillary plexus (SCP), and vascular density of deep retinal capillary plexus (DCP), nonperfused areas (NPAs) were evaluated with OCTA on baseline and after treatment. Results. The mean intravitreal injection number was 2.9 ± 0.89 times during six months in iRVO patients and 2.1 ± 0.86 times in non-iRVO patients, with statistically significant difference (p < 0.05 ). On baseline, central macular thickness (CMT) and FAZ were significantly thickened and enlarged compared to those of healthy fellow eyes; the vascular density of SCP and DCP were significantly decreased, and the differences were statistically significant (p < 0.05 ). Compared to baseline, after treatment, the best-corrected visual acuity (BCVA) was improved in either iRVO or non-iRVO (− 0.601 ± 0.387, − 0.241 ± 0.341 logMAR, p < 0.05 ). In iRVO, the improvement was more substantial than that of the non-iRVO group. FAZ in the non-iRVO group had significantly decreased compared to that in iRVO group (− 0.044 ± 0.040 versus 0.014 ± 0.043   m m 2, p < 0.05 ). CMT, the vascular density of SCP, and DCP had no significant difference. Conclusions. The changes of microvascular structure can be quantitatively evaluated by using OCTA for the patients with RVO. Conbercept had a significant effect on treatment of RVO with macular edema. A more profound effect was achieved in the iRVO group on visual improvement and FAZ reduction in the non-iRVO group after conbercept treatment.